Entre papéis, pessoas e perspectivas: etnografia da gestão da educação escolar indígena em Altamira PA - Santiago, Ana Elisa (2014)
This research intends to conduct an ethnography of the management of indigenous education in the municipality of Altamira (PA), that comprises nine ethnic groups (Arara, Araweté, Asurini, Curuaia, the Juruna, Kararaô, Parakanã, Xipaya, Xikrin) of Carib, Ge and Tupi languages. This region corresponds, according to the new configuration proposed by the Federal Government, the Territory Etnoeducacional 11, besides being one of the municipalities in the area affected by the Belo Monte Hydroelectric Complex in its installation process. The implementation of this management model and the compensation and indemnification means of the Power Plant has led to major changes that I followed and analyzed throughout this work. The field research was taken at the Altamira s Education Department, a privileged locus has allowed me to grasp different discursive positions: the Indians trying to understand what they expect from the school that is offered to them; the State their policies and guidelines proposed for these schools; and the Education Department staff responsible for making the indigenous education work and often come up against financial, bureaucratic and pedagogical boundaries. The intention here is to dialogue these areas, the Anthropology of the State and the Indigenous Ethnology, so that it can make a perspective enhance other. As Anthropology of the State, the ethnography in Indian school management does not hold only to official agencies for intervention and guardianship, but also analyzed how indigenous access (or not) these services. And as Indigenous Ethnology it paid attention to the operation of a public agency and how these people define and fight for their educational demands.